"For each time I remind myself of you, neither do I eat, nor do I drink, but I cry": family relations of Roman soldiers according to papyri - Ivanova, Elena Sergeevna (Genesis: исторические исследования, 2022)
The unique conditions of everyday life as well as special military traditions and mentality made family relations of Roman soldiers quite specific. Besides, the "marriage ban" or the lack of legal recognition of marriage contributed to the difficulties of militaries’ family life. Nevertheless, according to the data of epigraphy and papyrology, family played a key role in the life of Roman militaries. In this paper, the author's attention is focused on the information provided by papyrological sources. The object of the study is the papyrological letters of Roman soldiers to relatives. The subject of the study is the feelings and emotions of soldiers expressed in letters in relation to their family. The author also notes some practical issues of military family life, in particular, the problem of placing family members of a soldier on the territory of a military camp. Among the results of the study, it is worth noting the special sentimentalism of soldiers' letters revealed by the author. This feature should not be considered as a mere formality. The large numbers of emotional phrases are explained by the context of the era when most of people began to reflect on their duties and everyday being. In particular, they thought about the proper relationships between parents and children, husband and wife. Interestingly, one of the moral obligations in the relationships between close people became the presence of love. Moreover, this love should have been expressed in letters. Thus, despite the influence of the military ethos and other factors on the marital life of military personnel, the latter remained part of Roman society, for which family relations were one of the main values.